Characterization of antibiotic-resistant bacteria isolated from the Sultanah Aminah General Hospital wastewater treatment plant - Salehhuddin Hamdan 493758; Wan Azlina Ahmad, supervisor; Fakulti Sains 8004 (Sekudai : UTM, 1993)
Thesis (M.Sc) - Universiti Teknologi Malaysia, 1993